(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
The Variance-Gamma (VG) process is a three parameter stochastic process with respect to a Brownian motion. Here, we consider in our presentation, a detailed study of the VG process expressed as a difference of two gamma processes. As a result, we obtain the basic moments of the process using the characteristic function of the VG process with regard to the parameters of a differenced gamma processes. Also, the Levy-Khintchine formula for the process is derived via the Frullani’s integral. Finally, a modified European call option VG model incorporating a difference of two gamma processes is proposed.